Prestige vs. Reputation: Significance to Improve Public Perceptions towards Malaysian University - Ahmad, Jamilah; Ismail, Nurzali (Registrar of Newspapers for India (RNI), 2020)
Corporate image and reputation is an essential element in any business organization. However, not many studies have been done on service-oriented organizations, especially universities. For the university that seeks to improve its reputation, creating desirable images and positioning of a university’s image are important. This study obtained some interesting discoveries as well as answering the research objectives. The results suggest that the respondents had better perception of the university’s prestige than its reputation. A comparison between the mean values across two groups that is the university’s internal public and external public shows that the university’s internal public perceptions on prestige, personality, and reputation were relatively high. Public perceptions on each of the university’s image indicators were however moderate. This study also posits that the university’s internal public perception of the university image was significantly different from the external public. The university internal public had a high or positive perception of the university image, whereas the external public’s perception was only moderate. This study draws attention to the need for improving the external public’s perception of the university. This will remove the perception that university is just an ivory tower and doing something that may not be relevant to the industries and society need.